(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
One of the most divisivefigures in the recent history of Indian politics was none other than MuhammadAli Jinnah. He is still considered by many as the villain who was solelyresponsible for the creation of Pakistan. His story is a fascinating tale frombeing termed as an Ambassador of Hindu-Muslim unity in the initial days of hispolitical life and to be called the man who created Pakistan and the one whodivided India. His transformation and resulting political scenarios have leftbehind a deep legacy in the Indian minds. Jaswant Singh,a Cabinet Minister in AB Vajpayee’s Ministry, in his book “Jinnah: India, Partition, Independence”published in 2009 has squarely put the blame for partition of India in 1947 onJawaharlal Nehru, Sardar Vallabbhai Patel and the Congress rather thanQuaid-i-Azam Muhammad Ali Jinnah. In his book, he evokes momentous episodesthat set in motion the movement for partition of India besides the “epicjourney of Jinnah from being the ambassador of Hindu-Muslim unity, the liberalconstitutionalist and Indian nationalist to the Quaid-i-Azam of Pakistan”. On aquestion to whether Jinnah was a great man, he said, “Oh yes, self-made man whoresolutely worked towards achieving what he had set for himself.” Comparing theleadership of Gandhi and Jinnah, the book says, “Gandhi’s had almost anentirely religious provincial flavour while Jinnah’s was doubtless imbued by anon-sectarian nationalistic zeal”. Lal Krishna Advani, a staunch HinduNationalist, visited his birth place in Pakistan in 2005 when he praised Jinnahas being a secularist keeping in view his first Presidential speech on 11thaugust, 1947 to the constituent assembly of Pakistan. But, unfortunately hispolitical career began to decline after his comments on Jinnah. Keeping allthis in perspectives, the presentpaper is a humble attempt to contextualize and analyse MA Jinnah’s political ideasand his legacy.